Study on the Tooth Root Bending Stress Test of Hypoid Gear of the Driving Axle - Wang Kai; Tu Youyu; Zhao Wenhua; Li Kai; Xie Yi (Jixie chuandong)
In order to study the effect of dynamic load on the tooth root bending stress of hypoid gears,both static and dynamic test of hypoid gear bending stress of the driving axle are carried out by using electromotive strain method,which are compared and analyzed with results from finite element simulation. The static test shows that the tooth contact position is from the big side to small. The tooth root is under the application of tensile stress when the contact is begin while under compressive stress when the contact is finish. The stress value is consistent with the results of finite element calculation. The dynamic test shows that the mean value and amplitude of the maximum bending stress increased gradually with the increase of gear speed. This method is reliable and can be used in the reliability research on gear.